Analysis of Instrument Quality to Measure Scientific Reasoning and Halal Lifestyle on Human Digestive System Material: (Analisis Kualitas Instrumen untuk Mengukur Penalaran Ilmiah dan Halal Life Style pada Materi Sistem Pencernaan Manusia) - Umusalamah, N. Dede; Farida, Ida; Windayani, Neneng (BIODIK, 2025)
This study aims to analyze learning instruments on the human digestive system material in measuring scientific reasoning and the application of a halal lifestyle. High-quality and valid instruments are needed to obtain reliable data, so analysis of the instrument before use is an important step. This study focuses on the validity and reliability of the instrument designed to measure five indicators of scientific reasoning, namely: serial ordering, class inclusion reasoning, correlational reasoning, theoretical reasoning, and functionality reasoning. The research method uses a quantitative approach involving 30 students of class VIII MTsN 2 Subang as samples. Data were collected through written essay tests related to the human digestive system material. The results of the analysis using the ANATES application showed that the instrument had a high correlation (r = 0.78) and very high reliability (r = 0.87). Of the ten questions given, all were declared suitable for further research. These findings indicate that the developed instrument is effective for evaluating scientific reasoning and the application of a halal lifestyle in the context of biology learning.Keywords: halal lifestyle, human digestion, scientific reasoning